β-CPP bioceramics in alginate 3D scaffolds as a new material for mineralized tissue regeneration - Pinto, Gabriel C. [UNESP]; Piazza, Rodolfo D. [UNESP]; Mendes Soares, Igor P. [UNESP]; Anselmi, Caroline [UNESP]; Coimbra, Eduardo T.C.; Tavares, Paulo M.H. [UNESP]; de Souza Costa, Carlos A. [UNESP]; Hebling, Josimeri [UNESP]; Souza, Francisley Á. [UNESP]; Silva, Nuno J.O.; Guastaldi, Antônio C. [UNESP] (Elsevier, 2025)
Beta-calcium pyrophosphate (β-CPP) is a promising bioceramic for mineralized tissue engineering due to its intermediate biodegradation rate, osteoconductive properties, and superior ability to promote bone regeneration compared with traditional calcium phosphates such as hydroxyapatite (HA) and beta-tricalcium phosphate (β-TCP). This study investigated the development of a 3D scaffold composed of β-CPP and sodium alginate, a biocompatible polysaccharide that mimics the extracellular matrix (ECM). Sodium alginate interacts with calcium ions to form a gel-like structure, providing a supportive matrix for cellular activity. We evaluated the effects of various β-CPP concentrations within the alginate matrix on scaffold properties, focusing on cell adhesion, proliferation, and biomineralization. The results indicate that a β-CPP/alginate scaffold with a 5:3 weight-to-weight (w/w) ratio exhibited significantly greater mineralization activity than the control scaffold did, with the formation of interconnected cellular structures throughout the 3D matrix. This optimized scaffold promoted enhanced mineral deposition and maintained structural integrity under physiological conditions, achieving a balance between biodegradability and mechanical stability crucial for effective bone regeneration. These findings suggest that β-CPP, when incorporated into tailored scaffold compositions, holds significant potential for commercial bone graft applications, highlighting its ability to enhance tissue mineralization and cellular integration in next-generation bioceramic materials.
Keywords: 3D scaffolds; Bioceramics; Mineralized tissue; β-calcium pyrophosphates